A study to assess the feasibility of using hemolysis index to predict the corrected potassium in a hemolysed sample - Choudhury, Biswadeep; Karim, Nabiha Mayanaz; Chakraborty, Manidip (International Journal of Research in Medical Sciences, 2021)
Background: Potassium is one of the most commonly affected analytes in a hemolysed sample. Many formulae have been devised to predict the actual potassium in a hemolysed sample. This study was performed to compare the predicted potassium value in a hemolysed sample to that of potassium value in a non-hemolysed sample of the same patient. Methods: The hemolytic index (HI) derived equation from the paper by Dimeski et al was used to calculate potassium value in this study. A total of 99 paired samples were evaluated where the first sample in a pair was the hemolysed one and the other sample was a non-hemolysed one. Results: This study found that the potassium value in a sample and its respective HI have weak positive correlation. However, there was a statistically significant strong positive correlation between the estimated potassium of hemolysed sample to that of the potassium in the non-hemolysed sample. Conclusions: Hence, we conclude that it is feasible to use HI-derived equation to predict potassium in a hemolysed sample to avoid repetition of each sample.